Poll Everywhere E-Learning Platform, Test Anxiety, and Undergraduates’ Academic Performance in Mathematics: Empirical Evidence from Nigeria - Owan, Valentine Joseph; Bassey, Bassey Asuquo; Omorobi, Garieth Omorobi; Esuong, Uwase Uwase (American Journal of Social Sciences and Humanities, 2020)
The high rate of mathematics education students’ academic performance in universities has become unbearable. In an attempt to proffer solution to this menace, this study assessed Poll Everywhere eLearning platform, test anxiety, and undergraduates’ academic performance in Mathematics in Cross River State, Nigeria. The study adopted a quasi-experimental research one control group and one treatment group. The population of this study comprised all the fulltime regular undergraduates offering Education Mathematics in the Department of Science Education, University of Calabar, Calabar, Nigeria. Accidental sampling technique was adopted in selecting a sample of 328 undergraduates who are owners of smartphones from the population. Test-Anxiety Inventory and Mathematics Achievement Test (MAT) were used as data collection instruments. The null hypotheses were tested using independent t-tests and simple linear regression. Findings revealed that Poll Everywhere eLearning platform has a significant effect on students’ test anxiety and academic performance in Mathematics respectively; there is a moderate negative and significant relationship between students’ test anxiety and their academic performance in Mathematics. Based on the findings of this study, it was concluded that Poll Everywhere eLearning platform could be used for the effective teaching and examination of learners in Mathematics and other science-related disciplines. This can be done through the design and integration of course modules to the Poll Everywhere online platform.